(untitled) (Hematology Meeting Reports, 2009)
Mature B-cell tumors, such as chronic lymphocytic leukemia (CLL), are characterized by a redirection and reinforcement of microenvironment interactions that allow mature malignant B cells to avoid apoptosis and acquire better growing conditions. These interactions may be taken to explain why despite major therapeutic advances chronic B-cell malignancies are still incurable. CLL B cells are endowed with a functional B-cell receptor (BCR) that allows Ag interaction. Hence the concept of microenvironment as a regulator of malignant B-cell growth is tightly linked to the possible role of antigen (Ag) stimulation. The hypothesis that a BCRmediated stimulation plays a relevant role in the natural history of CLL is strengthened by the occurrence of somatic mutations of immunoglobulin heavy chain variable (IGHV) genes as well as by phenotypic and expression profiling signatures. CLL patients have a biased use of IGHV genes and subsets can be identified that carry stereotyped complementarity- determining region 3 (CDR3) sequences on heavy and light chains. The probability that two individual B-cells may express identical BCR is extremely low (10–9-10–12), indicating that the remarkable BCR similarity detected in more than 25% of unrelated and geographically distant CLL cases cannot be accounted for by pure chance. Further, as stereotyped CDR3 are more frequent in unmutated than in mutated CLL (about 40% vs. around 10% of the cases) it follows that antigenic exposure may be relevant in the pathogenesis of CLL, irrespective of IGVH mutational status. A whole range of investigation lead to believe that CLL B cells are Ag-experienced and suggest a central role for the recognition of a limited set of structurally similar epitopes in the selection and growth of leukemic clones.